The Story of Nelson : also "The Grateful Indian", "The Boatswain's Son" - Kingston, William Henry Giles, 1814-1880 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Story of Nelson" by William Henry Giles Kingston is a collection of short stories written in the late 19th century. The foremost tale centers around Lord Horatio Nelson, exploring his life and adventures at sea as recounted by a character who admired him, weaving together historical elements with a personal narrative. The other stories delve into different settings, such as farming in North America and a young boy's rise to naval ranks, reflective of the themes of bravery and the sea's challenges. The opening of the book introduces the narrative through a young boy's desire to become a sailor, which leads him to Greenwich Hospital to meet veterans who served under Nelson. The young narrator's admiration for Nelson is clear as he expresses his longing for adventure on the sea. This setting establishes a critical backdrop, as an old naval officer begins to recount his memories of Nelson, highlighting the captain's courage and charisma during pivotal moments in maritime history. In this way, the book sets the stage for exploring not only the iconic naval hero but also the world of seafaring life that shaped his legacy. (This is an automatically generated summary.)
Release date is 2007-11-16
Produced by Nick Hodson of London, England
Keywords: Children's stories; Indians of North America -- Juvenile fiction; Nelson, Horatio Nelson, Viscount, 1758-1805 -- Juvenile fiction; Seafaring life -- Juvenile fiction; Ship captains -- Juvenile fiction